Morphology and I-V Characteristics of Electrochemically Deposited Zinc Oxide on Silicon - Md Rashid, Ahmad Bukhairi; Zainal Abidin, Mastura Shafinaz; Abd Rahman, Shaharin Fadzli; Nawabjan, Amirjan (ELEKTRIKA- Journal of Electrical Engineering, 2021)
This paper reported on the electrochemical deposition of zinc oxide (ZnO) on p-silicon (p-Si) (100) substrate in the mixture of 0.1 M of zinc chloride (ZnCl2) and potassium chloride (KCl) electrolyte at a volume ratio of 1:1, 3:1 and 5:1 namely Sample A, B and C. The deposition process was done in room temperature with a current density of 10 mA/cm2 for 30 minutes. Prior to the experiment, all samples were treated by RCA cleaning steps. All samples were characterized using scanning electron microscopy (SEM) and energy dispersive X-ray (EDX). The results show that all samples have the same morphology of a flake-like structure with different Zn:O ratio that were 2.81, 2.35 and 2.49 for samples A, B and C. The current-voltage (I-V) characteristic graph was obtained by dark current measurement using Keithley SMU 2400 and the threshold voltage (Vth) values were determined at 2.21 V, 0.85 V and 1.22 V for sample A, B and C respectively which correspond with the Zn:O ratio where the highest value of Zn:O ratio can be found in sample A and the lowest in sample B. Based on these results, it shows that electrochemical deposition technique is capable of being used to deposit the flake-like structure ZnO on semiconductor material to form the p-n junction which behaves like a diode. The value of Vth seems to be depended on the ratio between Zn and O. Higher ratio of Zn and O will cause the higher value of intrinsic carrier concentration and built in potential which will increase the Vth value.